2005
DOI: 10.1111/j.1532-5415.2005.53425.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Individualized Fall Prevention Program on Fall Risk and Falls in Older People: A Randomized, Controlled Trial

Abstract: The individualized intervention program reduced some falls risk factors but did not prevent falls. The lack of an effect on falls may reflect insufficient targeting of the intervention to an at-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
138
1
30

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 42 publications
7
138
1
30
Order By: Relevance
“…Several studies have used physical exercise to improve older adults' static and dynamic balance [26][27][28][29][30][31] . Ballard et al 32 looked into the effect of a program of exercises and measures to reduce falling among 40 community-living older women.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used physical exercise to improve older adults' static and dynamic balance [26][27][28][29][30][31] . Ballard et al 32 looked into the effect of a program of exercises and measures to reduce falling among 40 community-living older women.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Lord et al 33 found no improvements in semi-static balance after an intervention program with individualized exercises that consisted of a 5 to 10 minute warm up, 30 minutes of group conditioning (strengthening, flexibility, coordination and balance exercises) and 10 minutes of individualized exercises (based on needs identified in evaluations), performed twice a week over 12 months. Another group received a minimal intervention through instruction sheets for exercises to perform at home, according to needs detected in an evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Ramsbottom et al 34 also failed to improve semistatic balance through a multicomponent training protocol performed twice weekly for 24 weeks. The hypothesis for the lack of improvement in semi-static balance after the completion of these training 33,34 protocols included insufficient intensity, exercises that were either unsuitable for the population studied (considering that individuals with different functional skills trained in the same group) or non-specific (exercises focused more on the dynamic aspects of balance at the expense of semi-static balance). The training protocols that were not successful were supervised studies without specific training, 8,34 those that used balance assessment positions that lacked sensitivity, such as a broad force platform base 35 , or those performed with insufficient intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Mortalität (van Haastregt, Diederiks, van Rossum, de Witte, Voorhoeve, & Crebolder, 2000;van Rossum, Frederiks, Philipsen, Portengen, Wiskerke, & Knipschild, 1993;Carpenter & Demopoulos, 1990), Muskelkraft (Woo, Hong, Lau, & Lynn, 2007;Lord, Ward, Williams, & Strudwick, 1995), Koordinationsfähigkeit (Woo et al, 2007;Lord et al, 1995), Reaktionszeit (Lord et al, 1995), Gehgeschwindigkeit (Steadman, Donaldson, & Kalra, 2003;Liu-Ambrose, Khan, Eng, Lord, & McKay, 2004;Woo et al, 2007), posturale Balance (Swanenburg, De Bruin, Stauffacher, Mulder, & Uebelhart, 2007), StandSitz-Performance (Lord et al, 2005), Knochendichte (Harwood, Sahota, Gaynor, Masud, & Hosking, 2004;Greenspan, Resnick, & Parker, 2003;Swanenburg et al, 2007) und allgemeiner Gesundheitsstatus (McMurdo, Mole, & Paterson, 1997;Carter et al, 2002;Barnett, Smith, Lord, Williams, & Baumand, 2003). Jedoch berücksichtigt die Begrenzung der Endpunkte auf klinische Parameter die Präferenzen der Zielgruppe nicht ausreichend (Langer et al, 2012;Nilsen, Myrhaug, Johansen, Oliver & Oxman, 2006;PCORI, 2012).…”
Section: Klientenzentrierte Endpunkteunclassified
“…Zu den bedeutenden klientenzentrierten Endpunkten zählen z.B. die Anzahl an Stürzen (McMurdo et al, 1997;Harwood et al, 2005;Lord et al, 2005;Porthouse et al, 2005;Swanenburg et al, 2007), die Anzahl an Gestürzten (McMurdo et al, 1997;Harwood et al, 2005;Porthouse et al, 2005), die Sturzangst (Porthouse et al, 2005;Lannin, Clemson, McCluskey, Lin, Cameron, & Barras, 2007;Lin, Wolf, Hwang, Gong, & Chen, 2007) sowie die Lebensqualität (Gallagher & Brunt, 1996;Harwood, Foss, Osborn, Gregson, Zaman, & Masud, 2005;Lannin et al, 2007) und Mobilität (Lannin et al, 2007). Da die individuelle Partizipation und Teilhabe von Klienten/-innen am Leben in der Gesellschaft Handlungsmaxime und fester Bestandteil der Sozialgesetzgebung (SGB IX) sind, sind Endpunkte, die soziale Partizipation und Wertvorstellungen abbilden, stärker in den Fokus zu rücken (BAR, 2008;Welti, & Fuchs, 2007).…”
Section: Klientenzentrierte Endpunkteunclassified